Mutational Studies of Gene HBB in β-Thalassemia Patients from Balochistan, Pakistan - Yousafzai , Asma; Nawaz, Faiza; Yousafzai, Asma; Luqman, Muhammad; Ahmed, Nisar; Arbab, Muneeza; Tabassum, Jamila; Ahmad, Jamil; Daud, Shakeela (Current Trends in OMICS, 2021)
Thalassemia is a hereditary blood disorder. It occurs due to two mutations in the HBB gene located on chromosome 11. This gene has 1606 base pairs and contains three exons. Moreover, HBB gene codes for β globin protein have been identified to posses 868 mutations, which comprise point mutation, insertion, deletion, and gene arrangement. In β thalassemia major, both alleles are mutated and no β chain is synthesized. In this study, three human families with thalassemia were selectedfrom different areas of Balochistan. For DNA extraction and estimation, 5 ml blood samples were extracted intravenously from the affected individuals, their normal siblings, and parents in 15ml falcon tubes containing 200μl EDTA. Primer sequences were designed on primer 3 for the mutational analysis of the HBB gene. Since the gene has a total of three exons and two introns, three primers, namely HBBX1, HBBX2 and HBBX3, were designed. These primers were used to amplify the HBB gene responsible for β thalassemia in all family samples. The amplified product was sequenced through an automated 3100 ABI Prism DNA sequence. The sequencing results were analyzed by the SaqMan software. This was done to determine if any genetic variable in the selected families showed mutations. In Family 1, 1 bp substitution mutation (c.9T>C) (p.his3his) and 1bp insertion (c.111T>G) (p.Ser10 val) in exon 1 of HBB gene were identified in thalassemia locus, while in in Family 2, 1bp substitution mutation (c.9T>C) (p.His3His) in exon 1 of HBB gene was identified in thalassemia locus. No mutation was observed in Family 03 after sequencing.